Vasopressin and oxytocin in sensory neurones: expression, exocytotic release and regulation by lactation - Dayanithi, Govindan; Forostyak, Oksana; Forostyak, Serhiy; Kayano, Tomohiko; Ueta, Yoichi; Verkhratsky, Alexei (Scientific reports, 2018)
The neurohormones arginine-vasopressin (AVP) and oxytocin (OT) synthesised in supraoptic and paraventricular nuclei of neurohypophysis regulate lactation, systemic water homeostasis and nociception. Using transgenic rats expressing AVP and OT tagged with fluorescent proteins we demonstrate that both neurohormones are expressed in sensory neurones both in vitro, in primary cultures, and in situ, in the intact ganglia; this expression was further confirmed with immunocytochemistry. Both neurohormones were expressed in nociceptive neurones immunopositive to transient receptor potential vannilloid 1 (TRPV1) channel antibodies. The AVP and OT-expressing DRG neurones responded to AVP, OT, 50 mM K+ and capsaicin with [Ca2+]i transients; responses to AVP and OT were specifically blocked by the antagonists of V1 AVP and OT receptors. Probing the extracellular incubation saline with ELISA revealed AVP and OT secretion from isolated DRGs; this secretion was inhibited by tetanus toxin (TeNT) indicating the role for vesicular release. Expression of OT, but not AVP in DRG neurones significantly increased during lactation. Together, the results indicate novel physiological roles (possibly related to nociception and mood regulation) of AVP and OT in the sensory neurones.
Keywords: fluorescence; Animals; Female; receptory oxytocinu; ženské pohlaví; laktace; Pituitary Gland, Posterior; nervové receptory; vasopresiny; Vasopressins; Exocytosis; oxytocin; Nociception; Sensory Receptor Cells; Oxytocin; dehydratace; Male; Ganglia, Spinal; Rats, Transgenic; exocytóza; Receptors, Oxytocin; zadní lalok hypofýzy; spinální ganglia; Receptors, Vasopressin; Dehydration; nocicepce; Fluorescence; zvířata; mužské pohlaví; Lactation; receptory vasopresinů; potkani transgenní